A search model for joint implementation - Giovanni Bella (Fondazione Eni Enrico Mattei (FEEM), 2009)
The aim of this paper is to present a search model in the field of environmental economics, where so-called clean and dirty producers enter the trading market, both looking for a partner with whom to exchange the goods they are endowed with. The model derived in this paper is rather simple. Nevertheless, it is able to produce a series of interesting results and useful insights, and is conveniently used here as a framework to explain the functioning of Joint Implementation programmes for polluting emissions' reduction.
Keywords: C61; O13; Q26; 330; Environmental economics; Search theory; Market failures